Practice makes perfect complete Italian grammar - Danesi, Marcel (Practice makes perfect, 2020)
"Focused on the practical aspects of Italian as it's really spoken, each chapter of Practice Makes Perfect : Complete Italian Grammar features clear explanations and numerous realistic examples. Dozens of varied exercises will build your understanding of the Italian language, while new vocabulary is introduced within the exercises and in convenient panels. This premium third edition is accompanied by audio recordings and flashcards, available online and via app, that will provide a new dimension and flexibility to your study" --Back cover